Kontribusi KKP UIN Mataram Dalam Meningkatkan Kesadaran Masyarakat Kembang Kerang Mematuhi Protocol Covid-19 - Al Kusaeri Al Kusaeri (Jurnal Participative: Jurnal Pengabdian Pada Masyarakat, 2021)
Since the enactment of the COVID-19 pandemic status by the World Health Organization (WHO) on March 11, 2020. Massive joint efforts are needed by the world community to fight the spread of the COVID 19 virus so as not to cause more victims. The crisis due to the spread of Covid 19 is not only seen as a health crisis, but affects crises in various sectors of public life, because the impact affects all sectors of life. Facing this, in addition to medical efforts by finding anti-viruses, public awareness of a healthy lifestyle is also needed, namely getting used to behavior following health protocols in carrying out various life activities to inhibit and stop the rate of transmission of Covid 19. Paying attention to the movement of the spread of Covid 19 which runs very fast Therefore, fast public awareness is also needed to get used to following the covid 19 protocol. For this reason, all levels of society must take part in increasing public awareness to carry out various activities by following the Covid 19 protocol including Higher Education, as the efforts that have been carried out by UIN Mataram through Participatory Work Lecture (KKP) activities in 2020